Sturge-Weber Syndrome Linked to GNAQ Mutation - J Gordon Millichap (Pediatric Neurology Briefs)
Investigators from Johns Hopkins School of Medicine, the Hugo W Moser Research Institute at Kennedy Krieger, Baltimore; Duke University; and Medical College of Wisconsin, Milwaukee, performed whole-genome sequencing of DNA from paired samples of tissue from 3 persons with the Sturge-Weber syndrome (SWS).